DETECTION OF PNEUMOCYSTIS CARINII (JIROVECI) FROM IRAQI PATIENTS WITH LOWER RESPIRATORY TRACT INFECTIONS (Iraqi Journal of Medical Sciences, 2016)
Background: Pneumocystis carinii is one of the rare fungi which cause pneumonia in immunocompromised patients. It is important to detect the fungus from the clinical specimens of suspected patients by laboratory tests.Objective:To identify Pneumocystis carinii from immunocompetent and immunocompromised patients with lower respiratory tract infections.Methods: This study included 300 patients suffering from lower respiratory tract infections of both immunocompetent (150) and immunocompromised (150) patients attending the Teaching Hospital in Mosul/Iraq. The clinical specimens collected were samples of sputum (247), and bronchial wash (80). The identification of Pneumocystis staining methods. Result:The organism was detected from 8 immunocompromised patients with pneumonia. Seven out of the 8 patients had carcinoma.Conclusion: Pneumocystis carinii is an opportunistic fungus which is an important pathogen in immunocompromised patients.Key words: Pneumocystis carinii (jiroveci), pneumocystis pneumonia, respiratory tract infection.
Keywords: Pneumocystis carinii jiroveci; pneumocystis pneumonia; respiratory tract infection